The relationship of adults’ memories of their childhood play with their children’s life satisfaction and attitude to the game of their children - Irina A. Ryabkova; Victoria M. Chernaya; Irina A. Kan (Современное дошкольное образование)
Background. The value of the children’s game lies in its developing potential, which determines the need to support it by adults, especially parents. Research indicates that such support contributes to better developmental outcomes in children. Moreover, parents can retain a love for play throughout their lives. Adults inclined toward playfulness report higher life satisfaction and greater engagement in life. Parental playfulness fosters spontaneity and creativity in parent-child interactions. It can be hypothesized that positive childhood play experiences influence adults’ life satisfaction and their attitudes toward their children’s play.